A remark on quasianalytic vectors for a pair of anticommuting operators - Tishchenko, S. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We prove that two self-adjoint operators that anticommute on the dense invariant domain of their common quasianalytic vectors are strongly anticommuting.